Prise en compte de la durabilité dans la représentation sociale de la croissance économique. - Hélène Blanc; Adeline Raymond (Développement Durable et Territoires)
This contribution analyses the social representation of economic growth and its evolution. The aim is to study how common sense appropriates scientific concepts. The expression of sustainable development is nowadays frequently present in the public debate, focusing attention on the sustainable dimension of human activities. We should therefore expect an integration of these ecological issues in consumption and production modes and consequently a modification of the social representation of economic growth. About 1200 students were questioned in 2004, 2006 and 2008. The results given by this data collection contradict our initial hypothesis and reveal an important stability of the social representation. No ecological factor is brought to light. The notion of growth seems to be appropriated as a crucial and unchanging value.